Change in Mobility: Consistency of Estimates and Predictors Across Studies of Older Adults. (27th August 2019) - Cornman, Jennifer C; Glei, Dana A; Weinstein, Maxine
Abstract: Objectives: This study compares estimates and determinants of within-individual changes in mobility across surveys of older U.S. adults. Methods: Data come from the Health and Retirement Study (HRS) and the Midlife in the United States (MIDUS) study. Measures of mobility comprise self-reported level of difficulty with walking several blocks, going up several flights of stairs, lifting and carrying 10 pounds, and stooping. Predictors include sociodemographic characteristics and indicators of health and health behaviors. We pool the datasets and estimate weighted lagged dependent variable logistic regression models for each activity, assessing cross-study differences using interaction terms between a survey indicator and relevant variables. Results: Estimates of declines in mobility differ substantially across surveys for walking, lifting and carrying, and stooping, but there are no between-survey differences in the probability of (not) recovering from a limitation. With the exception of age, determinants of change are similar between studies. For lifting/carrying and stooping, the age-related increase in developing limitations is less steep at younger ages for HRS respondents than MIDUS respondents, but steeper at older ages. Discussion: To compare estimates of mobility change across surveys, mobility measures would need to be harmonized. Determinants of mobility change, however, are more comparable.